Pani Bovary na Polesiu. „Pani Bovary" Gustave’a Flauberta a „Ulana" Józefa Ignacego Kraszewskiego (paralela) - Teklik, Natalia (Poznańskie Studia Polonistyczne. Seria Literacka, 2024)
This article presents a comparative analysis of the plot, character building and poetics in Gustave Flaubert’s Madame Bovary and Józef Ignacy Kraszewski’s Ulana. Flaubert and Kraszewski shaped the character of their protagonists in a similar manner in that both women attempt to, in line with the idea of bovarysme, become someone different that they truly are. What connects the two characters: Emma engrossed with sentimental novels and bored of provincial life and Ulana for whom an affair was supposed to be an escape from marital unhappiness, are certainly stubbornness, impetuousness and tendency to break social and moral conventions. The parallel between Flaubert and Kraszewski is further confirmed by an analysis of the formal layer of the two texts – both authors were realists devoted to insightful presentation of the meanders of the human psyche and to accuracy of character description.